Reduction of erythroid progenitors in protein-energy malnutrition - Borelli, Primavera; Blatt, Solange; Pereira, Juliana; de Maurino, Beatriz Beutler; Tsujita, Maristela; de Souza, Ana Cristina; Xavier, Jose Guilherme; Fock, Ricardo Ambrosio (Cambridge University Press, 2007)
Protein-energy malnutrition is a syndrome in which anaemia together with multivitamin and mineral deficiency may be present. The pathophysiological mechanisms involved have not, however, yet been completely elucidated. The aim of the present study was to evaluate the pathophysiological processes that occur in this anaemia in animals that were submitted to protein-energy malnutrition, in particular with respect to Fe concentration and the proliferative activity of haemopoietic cells. For this, histological, histochemical, cell culture and immunophenotyping techniques were used. Two-month-old male Swiss mice were submitted to protein-energy malnutrition with a low-protein diet (20g/kg) compared with control diet (400 g/kg). When the experimental group had attained a 20% loss of their original body weight, the animals from both groups received, intravenously, 20IU erythropoietin every other day for 14 d. Malnourished animals showed a decrease in red blood cells, Hb concentration and reticulocytopenia, as well as severe bone marrow and splenic atrophy. The results for serum Fe, total Fe-binding capacity, transferrin and erythropoietin in malnourished animals were no different from those of the control animals. Fe reserves in the spleen, liver and bone marrow were found to be greater in the malnourished animals. The mixed colony-forming unit assays revealed a smaller production of granulocyte-macrophage colony-forming units, erythroid burst-forming units, erythroid colony-forming units and CD45, CD117, CD119 and CD71 expression in the bone marrow and spleen cells of malnourished animals. These findings suggest that, in this protein-energy malnutrition model, anaemia is not caused by Fe deficiency or erythropoietin deficiency, but is a result of ineffective erythropoiesis.
Keywords: erythropoiesis; anaemia; protein malnourishment